2018
DOI: 10.3389/fpsyt.2018.00374
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Post-stroke Depression, Aphasia, and Physical Independence in Stroke Patients at 3-Month Follow-Up

Abstract: Objective: Few studies have examined the association between post-stroke depression (PSD), aphasia, and physical independence in Chinese patients. This study investigated the above association in stroke patients in China at 3-month follow-up.Methods: Altogether 270 patients within 14 days after ischemic stroke were recruited and followed up at 3 months. PSD, aphasia, and physical functional status were measured using the Stroke Aphasia Depression Questionnaire (SADQ), Western Aphasia Battery (WAB), and modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 62 publications
1
15
0
1
Order By: Relevance
“…The psychological health of patients with stroke is associated with the patients’ level of disability and dependence (Menon et al, 2017; Wang et al, 2018). In the current study, most patients with stroke were identified within 4 hr following admission as having depression (84.8%) and anxiety (86.9%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psychological health of patients with stroke is associated with the patients’ level of disability and dependence (Menon et al, 2017; Wang et al, 2018). In the current study, most patients with stroke were identified within 4 hr following admission as having depression (84.8%) and anxiety (86.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Such psychological states may lead to reduced motivation and low adherence to rehabilitation training and increased burden of caregivers. Both the depression and anxiety of patients with stroke and the caregiver’s burdens are associated with the patients’ level of disability and dependence (Menon et al, 2017; Wang et al, 2018). It could be conjectured that increasing muscle strength and functional status for patients with stroke early in their rehabilitation may lead to improved psychological health and reduced caregiver burden.…”
Section: Introductionmentioning
confidence: 99%
“…PSD tends to have more severe depressive symptoms than MD does [ 18 ]. Main symptoms of PSD are depressive mood, more cognitive impairment, apathy, less anhedonia, inappetence, less sleep disturbance, decreased energy, self-blame, self-mutilation and even suicidal tendencies [ 4 , 18 , 19 , 20 ]. Individuals with PSD have a disproportionally high prevalence of physical disability such as aphasia, motor/gait impairment and sensory losses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Language impairment is one of the clinical manifestations of stroke.The estimated prevalence of poststroke aphasia (PSA) ranges from 21% to 38% (Berthier, 2005). Patients with PSA suffer not only isolated social emotions (Kauhanen et al, 2000), depression (Bullier et al, 2020), and low quality of life (Wang et al, 2018) but also speech impairment.Speech impairment may be improved by using cortical stimulation or pharmacotherapy. However, half of PSA patients recover much or all
…”
mentioning
confidence: 99%
“…The estimated prevalence of poststroke aphasia (PSA) ranges from 21% to 38% (Berthier, 2005). Patients with PSA suffer not only isolated social emotions (Kauhanen et al, 2000), depression (Bullier et al, 2020), and low quality of life (Wang et al, 2018) but also speech impairment.…”
mentioning
confidence: 99%